KESIAPAN TENAGA KERJA DI KABUPATEN BADUNG DALAM MENGHADAPI MEA 2015 - Rustariyuni, Surya Dewi; Ayuningsasi, Anak Agung Ketut (PIRAMIDA, 2016)
Badung is one of the districts in the Province of Bali which has an increasing number of labor force in 2013 amounted to 333.46 thousand from the previous year amounted to 318.43 thousand people. The number of people who work in Badung increased in 2013 amounted to 330.89 thousand from the previous year amounted to 313.34 thousand people. This will lead to employment problems due to the lack of balance between demand and supply of labor in the country which will hamper the development process in Badung when labor in Badung district does not have the competence and competitiveness of the labor force compared with other ASEAN countries. After the enactment of AEC 2015 will be competition increasing labor and indispensable for improvement in the quality of human resources as critical success factors of development and progress of a nation. The workforce in the Badung regency is expected to have the ability and competitiveness in entering the era of AEC 2015.The purpose of this study to determine the implications of the Badung regency manpower in the face of AEC 2015, Badung regency manpower competence in the face of AEC in 2015, and workforce readiness Badung facing AEC. This research is descriptive qualitative study using primary data sources and data collection using questionnaires to workers from the 11 industrial sectors in Badung regency. With a sampling technique judgmental sampling method obtained a sample of 4,825 respondents 378 existing workforce. The results obtained on the implications of labor in the face of AEC Badung Regency: respondents who knew about ASEAN 79.6%, respondents who knew about the AEC as many as 253 people (66.9%), 29.6% of respondents obtain information about the AEC through television, 60. 8% of respondents agree with the imposition of the ASEAN Economic Community (AEC). Badung regency manpower competence in the face of AEC, 2015: Indonesian labor competencies able to compete with foreign workers 44.7%, of respondents have positive expectations to improve ahead of the implementation of AECs 38.9%. Confidence high labor would increase work ethic towards the AEC 44.7% and 210 respondents have the motivation to prepare for the challenges of the AEC. While self-employment readiness Badung facing AEC: 68.3% mastering the English language, Japanese Language 4.2% and 1.1% mandarin. About 51.1% of respondents were able to use a computer, 52.9% actively use the internet, 73.5% work well in a team work, 74.3% have a commitment to good work, and 68% were workaholic achieve employment targets given. This shows that the work ethic is very good employment indicator for the overall percentage of over 50%.
Keywords: competence; active population; competitiveness; the AEC